1995
DOI: 10.1002/dc.2840130109
|View full text |Cite
|
Sign up to set email alerts
|

Primary and metastatic high‐grade carcinomas of the salivary glands: A cytologic‐histologic correlation study of twenty cases

Abstract: We reviewed the clinical and fine-needle aspiration (FNA) findings in 20 patients with poorly differentiated carcinomas presenting initially as parotid or as submandibular masses. There were 11 primary tumors and nine metastatic malignancies in 14 males and six females ranging in age from 39 to 89 yr (median = 66). The tumor types included three primary carcinomas with oncocytic features, three additional cases of high-grade parotid carcinoma, one case of primary neuroendocrine carcinoma, two examples of malig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…Tumors with marked nuclear pleomorphism, prominent mitotic activity, or all but focal necrosis are usually interpreted as some other type of malignancy. 8 Thus, the distinction between high grade MEC and LG is largely FIG. 7.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors with marked nuclear pleomorphism, prominent mitotic activity, or all but focal necrosis are usually interpreted as some other type of malignancy. 8 Thus, the distinction between high grade MEC and LG is largely FIG. 7.…”
Section: Discussionmentioning
confidence: 99%
“…It is a very useful procedure in assisting clinicians in deciding whether a particular patient should be managed surgically. [1][2][3][4][5] The cytomorphologic features of most salivary gland lesions have been described. 4,7,8 The classic features of most salivary gland lesions, such as pleomorphic adenoma, adenoid cystic carcinoma, mucoepidermoid carcinoma, etc., are so characteristic that they are highly reproducible.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies from Europe, North America and Scandinavia have demonstrated its usefulness as a diagnostic tool in distinguishing surgical from nonsurgical cases, thus preventing unnecessary surgical procedures in some patients. [1][2][3][4][5] It is for this reason that the salivary gland is one of the most common sites of FNA biopsy. Although most cases show morphologic features very characteristic of specific entities, some lesions, both benign and malignant, can cause problems in interpretation.…”
mentioning
confidence: 99%
“…It is a safe, simple, cost-effective, accurate and minimal invasive for evaluation salivary gland lesions (Frable & Frable, 1991;Layfield & Glasgow, 1991;Cajulis et al, 1997;Buley & Roskell, 2000). It is not only useful in planning definitive preoperative diagnosis Sudarat Nguansangiam*, Somnuek Jesdapatarakul, Nisarat Dhanarak, Krittika Sosrisakorn but also can prevent unnecessary surgery procedures (Qizilbash et al, 1985;Layfield et al, 1987;Layfield & Glasgow, 1991;Stanley et al, 1995;Zhang et al, 2009). However, the management of patients with salivary gland lesions should not be based on cytology alone.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported the diagnostic performance of FNA in salivary gland lesions; the sensitivity was in the range of 62-100%; specificity of 86-100% and accuracy of 77-98.2% respectively (O'Dwyer et al, 1986;Frable & Frable, 1991;Chan et al, 1992;Zurrida et al, 1993;Al-Khafaji et al, 1998;Boccato et al, 1998;Mihashi et a., 2006;Tan & Koo, 2006). It is widely used in America, Europe and Asia (Layfield et al, 1987;Frable and Frable, 1991;Chan et al, 1992;Zurrida et al, 1993;Stanley et al, 1995;Al-Khafaji et al, 1998;Mihashi et al, 2006;Tan & Koo, 2006). Nevertheless, this procedure has been questioned for the diagnostic value in management of salivary gland tumors and may not cost-effective in routine cytology work for every patient (Batsakis et al, 1992;Tan & Koo, 2006).…”
Section: Introductionmentioning
confidence: 99%